2022
DOI: 10.3390/curroncol29060326
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain after Hormone Receptor-Positive Breast Cancer

Abstract: Obesity following breast cancer diagnosis is associated with poor overall survival. Understanding weight trajectories will help inform breast cancer survivors at greater risk of weight gain, and those who would benefit from earlier anti-obesity interventions. We performed a retrospective chart review of women from the Breast Cancer Program Longitudinal Repository (BCPLR) at Johns Hopkins diagnosed with hormone receptor-positive Stage I-III breast cancer from 2010 to 2020. We investigated obesity (measured by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The prevalence of obesity has been rapidly increasing in recent years 14 . Obesity contributes to cancer progression and unfavorable survival outcomes in BC patients 15,16 . However, available data on the effect of obesity on the prognosis of early‐stage BC patients undergoing SLNB, particularly in East Asian populations, are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of obesity has been rapidly increasing in recent years 14 . Obesity contributes to cancer progression and unfavorable survival outcomes in BC patients 15,16 . However, available data on the effect of obesity on the prognosis of early‐stage BC patients undergoing SLNB, particularly in East Asian populations, are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…14 Obesity contributes to cancer progression and unfavorable survival outcomes in BC patients. 15,16 However, available data on the effect of obesity on the prognosis of early-stage BC patients undergoing SLNB, particularly in East Asian populations, are scarce. Our findings found that obesity is an independent risk factor for prognosis in early-stage BC patients who had undergone SLNB; however, obesity did not affect the positive SLN rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations